Seroprevalensi Brucellosis dan Tingkat Gangguan Reproduksi Pada Sapi Perah di Kota Batu - Ani Setianingrum; Mira Fatmawati; Aulia Firmawati; Dahliatul Qosimah; Fidi Nur Aini E P Dameanti; Wahyu Islami; Utami Kurniawati; Lisa D Andriyani (Jurnal Ilmu Peternakan Terapan, 2020)
This study aimed to measure the incidence rate of brucellosis in dairy cattle at Batu City based onserological tests (seroprevalence) and to determine the relationship between the incidence ofbrucellosis and reproductive disorders. Cross-sectional epidemiological research was conducted todetermine the prevalence of brucellosis in dairy cows. Serum samples were obtained from 130dairy cows over 6 months of age, reproductive disorders data using a questionnaire on 21 farmers.Serological testing used the Rose Bengal Test (RBT) and continued with the Complement FixationTest (CFT). The data analysis used Pearson's Chi-Square correlation statistical test. Theseroprevalence of brucellosis at Batu City was 0.7%. The prevalence of reproductive disorders indairy cows was 29.2% consisted of 8.5% abortion and 20.8% repeated mating. There was acorrelation between brucellosis and the incidence of abortion (ï£2 = 10.90; P<0.05) and a correlation between the incidence of abortion and the age more than 3 years (ï£2 = 5.35; P<0.05). The conclusion of this study showed that the prevalence of brucellosis at Batu city was low (<2%).The results of this study could be used as the basis for implementing a vaccination program anderadicating brucellosis at East Java